Unfolding the Role of Economic Variables on SDGs and Ecological Footprint in SAARC Economies since 2000-2021 - Gautam, Ajay Kumar; Verma, N.M.P (Journal of Environmental and Energy Economics, 2025)
The paper describes the importance of overall score of sustainable development goals (SDG) and mitigation of ecological footprint in SAARC economies the basis of real variables. Adoption of renewable energy for independence on energy needs, economic growth and consideration of the globalization for sustainability plays a crucial role on SAARC economies. Moreover, some prior work has also examined this issue, but the focus was more on the ecological footprint as an indicator of sustainability of the economy. This study examines the two key elements of the works in this area. Firstly, ecological footprint and secondly, overall score of sustainable development goals as impacted by renewable energy consumption, economic growth and globalization in SAARC economies from 2000 to 2021. Use of advanced econometric approaches, namely Panel-Corrected Standard Errors (PCSE), Feasible Generalized Least Squares (FGLS), and Driscoll-Kraay estimators, are used to handle the heterogeneity and cross-sectional dependence which are common in panel data in order to guarantee error free results. The most significant observations of this study are: Firstly, renewable energy consumption have double-edged causation on ecological footprint and overall score of sustainable development goals in SAARC economies. Secondly, globalization reduces ecological footprint and increases overall score of SDG. Finally, economic growth increases ecological footprint and reduces overall score of SDG. These observations are aligned with PCSE, FGLS and Driscoll-Kraay estimation at 1% level of significance. Further, a significant number of explanatory variables have a unidirectional relationship on ecological footprint and overall score of SDG except renewable energy consumption. Further as revealed by the Dumitrescu-Hurlin panel causality test which indicates a need to take action in order to improve overall score of SDG and mitigate ecological footprint SAARC economies to harness renewable energy resources through investment on R&D and green technologies in substantial manner.